2017
DOI: 10.1021/acs.cgd.6b01845
|View full text |Cite
|
Sign up to set email alerts
|

Structural Induction via Solvent Variation in Assemblies of Triphenylboroxine and Piperazine—Potential Application as Self-Assembly Molecular Sponge

Abstract: This study examined the direct effect of solvent on the chemical composition and structure of supramolecular assemblies formed from triphenylboroxine ((PhBO) 3 ) and piperazine (ppz) through N→B bonds. Oxygen-containing solvents with a molecular size smaller than 4.1 Å produce 1D polymeric structures (1:1 boroxine/piperazine) of compositions {(PhBO) 3 (ppz)} n •nTHF (1a• THF) and {(PhBO) 3 (ppz)} n •nAcetone (1a•Acetone), in which the boroxine B 3 O 3 rings are linked through N→B bonded piperazine molecules in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 96 publications
0
28
0
Order By: Relevance
“…The yields of cyclic carbonates decreased to 78%, 50%, and 43% for butylene oxide, 1,2-epoxy-3-allyloxypropane, and glycidyl phenyl ether, respectively (Table ). This may be related to the slow diffusion of large-sized substrates into the framework with the increase of molecule size from 4.2 × 2.6 × 1.8 Å 3 of propylene oxide to 9.4 × 4.3 × 2.3 Å 3 of glycidyl phenyl ether . Moreover, the interaction strength between the substrates and the active sites may also affect the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The yields of cyclic carbonates decreased to 78%, 50%, and 43% for butylene oxide, 1,2-epoxy-3-allyloxypropane, and glycidyl phenyl ether, respectively (Table ). This may be related to the slow diffusion of large-sized substrates into the framework with the increase of molecule size from 4.2 × 2.6 × 1.8 Å 3 of propylene oxide to 9.4 × 4.3 × 2.3 Å 3 of glycidyl phenyl ether . Moreover, the interaction strength between the substrates and the active sites may also affect the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…10 g , h Recently, the B←N dative bond has appeared to serve as a good alternative to traditional non-covalent and metal–coordinate bonds, to build supramolecular network/host–guest-based crystalline assemblies, for various applications. 11–20 In general, the donation of electrons from the N-donor ligand to the electron-deficient boron atom (empty p-orbital) stabilizes such type of bonding. It has also been observed that the electronic properties of the interacting partner strongly influence the strength of the B←N dative bond.…”
mentioning
confidence: 99%
“…The Laplacian vs distance plot (see Figure 6a in ref ) shows a “heap”, where the Laplacian changes its sign, and this corresponds to the overall lability of this particular bond. This feature has recently been used to construct various B–N bonded networks …”
Section: Results and Discussionmentioning
confidence: 99%
“…in ref122) shows a "heap", where the Laplacian changes its sign, and this corresponds to the overall lability of this particular bond. This feature has recently been used to construct various B−N bonded networks 128. Similarly to the B−N case, all B−O bonds exhibit the closedshell character, which is manifested by the positive Laplacian.…”
mentioning
confidence: 99%